Enculturation of Modeling Behavior to Form the Religious Attitude of Students of Pesantren Jagat Arsy Tangerang - Siti Munawati; Siti Nurislamiah; Ariesta Setyawati; Saiful Saiful; Yuni Ratna Sari (Ta'dib: Jurnal Pendidikan Islam, 2023)
Pesantren Jagat Arsy is one of the Islamic boarding schools in South Tangerang Regency, Banten Province that implements a religious learning system using the modeling behavior method. Students are taught how to behave in accordance with the behavior of the teacher as an educator who becomes a model figure for students or students. In this case the researchers wanted to examine how the enculturation of modeling behavior in shaping the Islamic tradition of students with religious attitudes at Pesantren Jagat Arsy. In this study, a descriptive qualitative research method, with observation and interview data collection techniques was implemented. Interviews were conducted with 4 boarding school teachers, and to determine these teachers, purposive sampling techniques were used. After the data were collected, they were then analyzed using qualitative data analysis technique suggested by Miles and Huberman. The results of the study based on the results of interviews and observations concluded that Pesantren Jagat Arsy education prioritizes moral and moral improvement with religious guidance through the modeling behavior method of the teachers. The influence of teacher figures at Pesantren Jagat Arsy is really high in shaping the religious attitudes of students related to behavior and moral values.